Extension of the A-UNIFAC model to mixtures of cross- and self-associating compounds - Ferreira, Olga (2005)
http://apps.isiknowledge.com/full_record.do?product=UA&search_mode=GeneralSearch&qid=4&SID=V21Di6PajaHLPoM3@AJ&page=1&doc=1&colname=WOS